2017
DOI: 10.1002/hep4.1105
|View full text |Cite
|
Sign up to set email alerts
|

Progression of liver fibrosis is associated with non‐liver‐related mortality in patients with nonalcoholic fatty liver disease

Abstract: In patients with nonalcoholic fatty liver disease (NAFLD), prognosis and outcome, especially non‐liver‐related mortality, remain incompletely elucidated. We clarified the mortality from all causes in patients with NAFLD. A total of 4,073 patients with NAFLD diagnosed by ultrasonography were enrolled. We investigated the causes of death and analyzed the mortality from non‐liver‐related diseases according to the degrees of steatosis and fibrosis using the competing risk method. We used the NAFLD fibrosis score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
3
36
2
Order By: Relevance
“…We acknowledge that there is no currently available longitudinal data to examine the correlation between worsening noninvasive fibrosis markers and histological progression of fibrosis stage over time. NFS and FIB‐4 are the most widely used noninvasive fibrosis markers in the setting of NAFLD . However, these non‐invasive fibrosis markers include variables in the formula that may affect the association between obesity and fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that there is no currently available longitudinal data to examine the correlation between worsening noninvasive fibrosis markers and histological progression of fibrosis stage over time. NFS and FIB‐4 are the most widely used noninvasive fibrosis markers in the setting of NAFLD . However, these non‐invasive fibrosis markers include variables in the formula that may affect the association between obesity and fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of hepatic steatosis has great clinical importance. In patients with NAFLD, the degree of hepatic fibrosis is the most important factor related to mortality . However, it has also been reported that hepatic steatosis can progress to non‐alcoholic steatohepatitis and clinically significant fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with NAFLD, the degree of hepatic fibrosis is the most important factor related to mortality. 7,8 However, it has also been reported that hepatic steatosis can progress to non-alcoholic steatohepatitis and clinically significant fibrosis. In hepatitis C, hepatic steatosis is associated with more severe fibrosis and rapid disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lazo et al 8 found no association between ultrasound diagnosed NAFLD and increased risk of all-cause, cardiovascular or cancer mortality outcomes. In addition, reports from studies with ultrasound diagnosed FLD suggest increased scores of algorithm-based assessed markers of fibrosis are associated with different mortality outcomes among NAFLD subjects 9–11. However, reports from studies using algorithm-based surrogate of fatty liver suggest disparate associations 12–15.…”
Section: Introductionmentioning
confidence: 99%